INVESTIGATION OF ANTI-ARTHRITIC ACTIVITY OF SUSTAINED RELEASED TABLET OF DIFFERENT HERBAL PLANTS BY USING IN VIVO AND IN VITRO MODELS (Journal of Pharmaceutical Negative Results, 2023)
Objective: According to statistics, one third of the population is statistically affected by arthritis, making it a very common disorder. The purpose of the current study is to determine the effectiveness of herbal plants in treating arthritis.Methodology: The carrageenan induced arthritis model was used to evaluate the in vivo anti arthritic activity of sustained-release tablet of herbal plants. The in-vitro protein denaturation method was used to examine the anti-arthritic activity. The result was evaluated spectrophotometrically at 660nm against the reference drug diclofenac sodium. The sustained-release tablet of herbal plants was incubated with bovine serum albumin for complete denaturation.Result: In contrast to the standard medication, diclofenac sodium, the results showed that the sustained-release tablet of herbal plants had significant anti-arthritic activity and that the extract inhibited protein denaturation at concentrations of 200 g/ml to 1000 g/ml.